Superconductivity mediated by polar modes in ferroelectric metals - C. Enderlein (Nature Portfolio, 2020)
Superconductivity in doped SrTiO3 near to a ferroelectric quantum critical point emerges due to a strong interaction driving the formation of Cooper pairs, the nature of which has remained elusive for several decades.  Here, the authors reveal that pairing is due to the exchange of longitudinal hybrid polar modes rather than transverse critical modes.